2021
DOI: 10.5937/poljteh2103001i
|View full text |Cite
|
Sign up to set email alerts
|

A review of common natural ventilation and evaporative cooling systems for Greenhouses and the Nigerian reality

Abstract: Greenhouses simulate the "desired" environment for successful growth and development of plants. They, by design, achieve this desired environment by supplying the necessary climatic inputs needed by the plants to strive and at the same time exclude factors impeding the growth of plants, hence it is called a controlled environment. One of the common and most desired attribute of the greenhouse is its ability to provide effective cooling to the plants. This paper reviewed, extensively, the concept of evaporative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Conversely, the use of red LED light was found to be inappropriate as it negatively affected the physical properties of the mushrooms and resulted in low yields. Mondal et al [13] reported in their study that longer stipe lengths and smaller pileus diameters were associated with exposure to red light, which resulted in poor mushroom quality. Thus, it can be inferred that LED light colours are a critical factor in enhancing the overall performance and yield of white oyster mushroom cultivation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Conversely, the use of red LED light was found to be inappropriate as it negatively affected the physical properties of the mushrooms and resulted in low yields. Mondal et al [13] reported in their study that longer stipe lengths and smaller pileus diameters were associated with exposure to red light, which resulted in poor mushroom quality. Thus, it can be inferred that LED light colours are a critical factor in enhancing the overall performance and yield of white oyster mushroom cultivation.…”
Section: Discussionmentioning
confidence: 96%
“…The fan facilitated the movement of air, drawing it through the wet cooling pad and exhausting it out of the chamber. This created a continuous flow of air, promoting the evaporation process and maintaining a controlled temperature environment [13] for mushroom growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the relative humidity of the storage environment will slow down the rate of water loss. The best method to increase relative humidity is to lower the temperature (Ikechukwu-Edeh et al, 2021;Vakiloroaya et al, 2014). Therefore, the aim of this study was to design an evaporative cooling system for the temporary storage of harvested fruits and vegetables in order to increase shelf life before distribution (Ali, 2020;Shashua-Bar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%